Edifying In The Industrial Revolution 4.0 With The Role Of Islamic Education - Rivaldy Hermansyah; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - The purpose of research is to know the role of each individual and strategy in promoting chastity education in the industrial 4.0. The focus of this research problem is on how role concepts and moral education strategies are carried out by individuals in the industrial 4.0. This type of research is qualitative work with a descriptive qualitative approach. Research shows that people with far less sexual education, the very understanding of islamic religious science is so limited that ahklak education is very limited, and the concept of sexual education is to lead an example and give an inoffensive knowledge to each individual.